The challenges of managing and leading diverse workforce: Equity and job satisfaction - Zhao, Qianwen (2019)
In the last decade, the expansion of the global market and multinational corporations have resulted in the increase of the diverse workforce. Hiring a diverse workforce is seen as a necessity for every multinational organizations. Organizations with a diverse workforce are better able to meet the needs of the international market and it provides the organization with a unique competitive advantage, however, diverse workforce also bring challenges for multinational organizations, which requires organizations and managers to adopt effective management strategies. This qualitative study compares the experiences of employees and managers in different multinational organizations to investigate the advantages and challenges of diverse workforce in terms of equity and job satisfaction. From analyzing the findings, diverse workforce faces challenges in aspects of wage and treatment gaps, trust crises, ethnocentricity and communication. The study also analyzes the solutions that how to deal with those challenges. The results provided insights into effective strategies of diversity management. As the development of a global market, the debate surrounding the diverse workforce and diversity management proliferates.